PENGARUH IDEALISME DAN REALISME TERHADAP PENDIDIKAN - Ari Wawan Dermawan Ari; Siti Fadjarajani (PT. Jurnal Center Indonesia Publisher, 2025)
Idealism and realism are two opposing philosophies that have shaped the field of education for centuries. These two philosophies have significantly influenced educational practices and curriculum development, with educators often incorporating elements of both idealism and realism into their teaching methods. The method used in this study is a literature review, which involves searching for literature from both international and national sources using tools like QuillBot. This literature study examines the relationship between relevant writings and supporting literature, such as books, journals, articles, theses, and other relevant sources found on the internet. The results of this study show that the integration of idealism and realism in education is crucial to providing students with a comprehensive and effective learning experience. By balancing a focus on ethical values and practical skills, educators can help students develop the tools they need to thrive in both academic settings and the real world.